Active and latent forms of transforming growth factor beta activity in synovial effusions (The Rockefeller University Press, 1989)
We have evaluated the possible involvement of TGF-beta in rheumatoid arthritis by assay of 16 cell-free synovial fluids for the presence of its active and "latent" forms. Evidence has been obtained for TGF-beta- like activity in synovial effusions by four criteria: (a) TGF-beta receptor competition, (b) soft-agar colony formation of AKR-2B and NRK- 49F indicator cells, (c) immunological neutralization of the biological activity, and (d) biochemical activation of a latent form.